Assess the Role of Sonography and MRI in Diagnosing Ovarian Masses - G. Mahender Reddy; M. L. Ravindernath; S.Snehaja Reddy (Asian Journal of Medical Radiological Research, 2020)
Background: In order to conduct appropriate surgical treatments, the characterization of ovarian lesions is of considerable significance and can affect patient care. A multidisciplinary approach based on physical assessment, laboratory tests and imaging techniques includes adequate measurement of the adnexal masses. The aim is to assess the role of Sonography and MR in diagnosing ovarian masses, to study imaging characteristics of ovarian masses on USG and Doppler in correlating these findings with MR features. Subjects and Methods: The present study was carried out in the department of radiodiagnosis to determine the efficacy of sonography and MRI in the diagnosis of ovarian masses. The study group comprised 50 patients with clinically suspected ovarian masses and imaging was carried out on all patients with ovarian masses and imaging was carried out on all patients with ovarian masses. All the masses were evaluated on sonography based on the Sassone scoring system. Morphological analysis was performed for each mass based on wall thickness, inner wall structure, septal structure and echogenicity of mass. The color flow was carried out, subsequently; MRI was carried out for each patient. Radiological diagnosis was confirmed after surgery on histopathological examination. Results: The majority of the patients were in the age group of 31-40 years. The most common symptoms noted were pain in the abdomen. The most common clinical finding was a palpable mass. The application of Sassone sonomorphologic score >9 was identified in 8 masses, out of which 7 were malignant and 1 was a benign lesion. The colour flow was detected in 38 out of 50 masses. The presence of flow, type of flow, vessel arrangement, morphology and location were noted and on pulsed Doppler the RI and PI values were calculated. Out of 8 malignant cases, 5 were diagnosed as malignant according to the Caruso score. The overall sensitivity 100 %, specificity is 97.6% and diagnostic accuracy is 98% of MRI which is higher than that of ultrasound and CDS. Conclusion: We conclude that MRI is a superior diagnostic modality in establishing the diagnosis of ovarian masses.